Ampicillin sulbactam resistance pattern as a first-line drug in children - Putrawan, Oka; Rejeki, IGAA Putri Sri (Folia Medica Indonesiana, 2016)
Infection often occurs in children with malignant hematology and causes morbidity and mortality. Antibiotics should be given based on the results of culture and antibiotic susceptibility test. Ampicillin Sulbactam is a first-line drug in children with infection. The purpose of this study was to obtain an objective overview of Ampicillin Sulbactam resistance patterns of culture in patients hospitalized in pediatric Hemato-Oncology Ward, Dr Soetomo Hospital, Surabaya. This was a descriptive study. Data on culture and susceptibility test result to Ampicillin Sulbactam were taken from medical records of those patients between September 2012 - February 2013. There were 342 culture examinations in 88 patients (44 girls and 44 boys). Most of the children aged <5 years (58%). Growth of bacterial cultures was obtained in 83 namely Escherichia coli, Burkholderia cepacia, and Klebsiella oxytoca (Gram-negative) and coagulation negative Staphylococcus (CONS), Staphylococcus aureus, and Staphylococcus saprophyticus (Gram-positive) were found in blood culture. Staphylococcus aureus (Gram positive) and E. coli, Klebsiella pneumoniae, and B.cepacia (Gram-negatif) were found in urine. The result of antibiotic susceptibility test culture showed resistance to Ampicillin Sulbactam in E. coli (69%), Burkholderia cepacia (85%), CONS (50%), Staphylococcus aureus (25%), K. pneumoniae (85%), Klebsiella oxytoca (50%), and P. aeroginosa (67%). There was ampicillin sulbactam resistance in children hospitalized in pediatric Hemato-Oncology Ward, Dr Soetomo Hospital, Surabaya against E. coli (69%), Burkholderia cepacia (85%), CONS (50%), Staphylococcus aureus (25%), K.pneumoniae (85%), and Klebsiella oxytoca (50%), P. aeroginosa (67%).